أحكام تأديب الزوجة عند نشوزها في الفقه الاسلامي - بوقنة, مروى (University of Eloued جامعة الوادي, 2018)
"ملخص العربية إنّ موضوع هذا البحث الموسوم بأحكام تأديب الزوجة عند نشوزها في الفقه الإسلامي؛ تناول قضية من القضايا الحساسة في شأن الأسرة، والعشرة بين الزوجين، وهو النشوز من قبل الزوجة، وكيفية علاجه من قبل زوجها على النهج الصحيح. وقد جاء هذا الموضوع في ثلاثة مباحث: خُصِّصَ أوله لبيان لِتعريف النشوز وبيان حكمه وأسبابه وحالاته، وعُنِيَ ثانيه بتعريف تأديب الزوجة، وبيان مشروعيته وشروطه ووسائله، وجُعِلَ ثالثُه لمسقطات تأديب الزوجة، والضرر الناتج عن التأديب، ومسائل مختلفة متعلقة بتأديبها. وتُوِّج البحث في ختامه ببعض النتائج والتوصيات منها: أن للزوج على زوجته وَلاية التأديب إن خَالَفَته فيما يَجِب عليها من طاعة، وأن للتأديب وسائل محدودة، وهي المذكورة في القرآن الكريم؛ الوعظ، والهجر، والضرب. " "Abstract: Subject of this research which is entitled: regulations of correction of the wife in case of desobeidance in the Islamic jurisprudence. It has dealt with one of the sensitive family issues and the marital cohabitation, which is the desobedience from the wife and how it must be dealt with by the husband in the right way. This study came into three sections: The first one defined the desobeidance and its verdict, its cause and different cases. Whereas the second was about the definition of wife's correction and the evidence of its legitimacy, its conditions and the used means. The third one is an outline of the correction of the wife and the harm it may cause, and different issues concerning her correction. The study ended up with some results and recommendations, some of them are: The husband has the right to correct his wife if she violates orders she should be obeying. This correction is a limited mean that is mentioned in the holy Coran: preaching, abondoning, beating. "
مذكرة ماستر تخصص فقه وأصول
Keywords: النشوز- تأديب الزوجة- الزوجين; Nchuz - discipline wife - spouses